Estudo da série LaNi1-xFexO3 e folhas de grafite pirolítico em reações de desprendimento de oxigênio - Gozzo, Cipriano Benedito (Universidade Federal de São Carlos, 2020)
Due to the critical need to change from fossil to renewable fuels, the perovskite oxide structures emerge as an important class of materials due to its activity in photovoltaic cells, photocatalysis, photoelectrochemical cells and electrocatalytic performance for oxygen evolution reactions (OER). Among several perovskites, LaNiO3 is promising for water oxidation reactions. However, this material presents some difficulties in stabilizing the Ni3+ site. A possible alternative to stabilize this oxidation state is the addition of other transition metals. The support electrodes on which the materials are deposited and used in RDO are extremely important in improving electrocatalytic activity. Pyrolytic graphite sheets can present themselves as an attractive alternative for a support electrode, having advantages as excellent electrical conductivity. Therefore, in this work, a study was carried out on the electrocatalytic properties of the LaNi1-xFexO3 series (x = 0.0, 0.3, 0.6 and 0.9) for RDO, analyzing the effects caused by the addition of Fe3+. These materials were deposited on PGS, as a potential substrate for electrocatalysis. Perovskites were synthesized by the coprecipitation method, followed by heat treatment. Depending on the amount of iron added, a phase transition from rhombohedral to orthorhombic, and morphological modifications were identified in these materials. It was observed that the LaNi0.4Fe0.6O3 electrode presented the most efficient condition for RDO. This electrocatalyst showed the lowest charge transfer resistance, low overpotential (439 mV at 10 mA cm-2) and a lower Tafel slope (52 mV dec-1) compared to the LaNiO3 phase (465 mV and 76 mV dec-1). PGS was also used for electrodeposition of NiFe-based catalysts, which presented a high electrocatalytic activity. The electrodeposited sample with 75% Ni and 25% Fe provided an overpotential of 320 mV, while in the same sample deposited on glassy carbon, the overpotential was 350 mV. In conclusion, it was possible to determine that both the LaNi1-xFexO3 series (x = 0.0, 0.3, 0.6 and 0.9) and NiFe layered double hydroxides, both deposited on PGS, are potential materials to be applied in OER.
Study of the LaNi1-xFexO3 series and pirolytic graphite sheets in oxygen evolution reactions
Keywords: Reação de desprendimento de oxigênio; Energias renováveis; Eletroquímica; Perovskitas LaNi1-xFexO3; Folhas de grafite pirolítico; Oxygen evolution reaction; Renewable energy; Electrochemistry; Perovskites LaNi1-xFexO3; Pyrolytic grafite sheet; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::CINETICA QUIMICA E CATALISE; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::ELETROQUIMICA